Interspecies interactions among sugarcane-associated bacteria and their impact on plant growth promotion traits - Fascio, César Justiniano; Rubio Molina, Anna Carolina; Marin-Gallego, Benyi Juliana; de Cristóbal, Ricardo Ezequiel; Espinosa-Urgel, Manuel; Vincent, Paula Andrea; Farizano, Juan Vicente; Adler, Conrado (Frontiers in Microbiology, 2026)
Microbes associated with plants have proven to play a fundamental role in their growth and phytosanitary status. Microbial community architecture and function results from interactions with the host and with each other. Therefore, microbial diversity and the array of possible interspecies interactions should be considered as key elements for the development of future biocontrol and crop improvement strategies. To gain some insight into this potential, we isolated 16 rhizospheric and 16 endophytic bacteria from sugarcane and tested their ability to interact with each other. To this end, we performed 120 pairwise interaction assays within each group. Although most interactions were neutral in both rhizospheric and endophytic communities, negative interactions were more frequent between rhizospheric isolates. In contrast, positive ones predominated among endophytic isolates. After determining the interaction phenotypes between isolates, we tested their impact on plant growth promoting (PGP) traits and biocontrol against Xanthomonas albilineans. Our results demonstrate that interspecies interactions among sugarcane-associated bacteria can modulate key PGP traits regardless of their interaction phenotype, highlighting a potentially overlooked layer of functional regulation within the microbiome. Accordingly, social behavior of microorganisms might set the basis for a rational design of performance-improved bioinoculants for agriculture, particularly consortia-based inoculants.